A PEDAGOGICAL MODEL FOR THE CONSTRUCTION OF KNOWLEDGE THROUGH COLLABORATIVE LEARNING IN THE ERA OF CONNECTIVITY - Barrientos, Rosa Aleida Gómez; Villamizar-Carrillo, Anyela Patricia; Gáfaro, Richard Eliseo Mendoza (Journal of Posthumanism, 2025)
In the digital age, the integration of social networks into pedagogical practices presents an opportunity to transform traditional educational models. This study addresses the need to design a pedagogical model that facilitates collaborative learning mediated by technology in Colombian secondary education.To develop a pedagogical model that incorporates social networks into classroom practices, fostering collaborative learning environments and promoting the active construction of knowledge.The research follows a qualitative, interpretative paradigm with an ethnographic and phenomenological approach. Data were collected through semi-structured interviews and participant observation within the Presbítero Álvaro Suárez Educational Institution, Villa del Rosario, Colombia. Categorization and hermeneutic analysis were applied to derive key insights.The findings reveal a lack of integration of social networks in current pedagogical practices, due in part to rigid institutional structures and insufficient teacher training in digital tools. However, students demonstrate high potential for collaborative engagement when digital media are meaningfully incorporated.A pedagogical model based on the responsible use of social networks can enhance motivation, creativity, critical thinking, and the construction of collective knowledge. For such transformation to be effective, institutional commitment and comprehensive teacher training are essential.